Guidelines for Best Practice of Augmented Reality in Websites Emphasizing Usability - Souza, Andrea Silva [UNESP] (2015)
This short paper aims to show the beginning of an research on augmented reality (AR) applied in websites, emphasizing usability in data visualization and the intuitive aspects of the interface.